Associations of Lumber Disc Degeneration With Paraspinal Muscles Myosteatosis in Discogenic Low Back Pain - Huang, Yilong; Wang, Ling; Luo, Baofa; Yang, Kaiwen; Zeng, Xiaomin; Chen, Jiaxin; Zhang, Zhenguang; Li, Yanlin; Cheng, Xiaoguang; He, Bo (Frontiers in Endocrinology, 2022)
Accompanied with intervertebral disc (IVD) degeneration, increasing fat infiltration of paraspinal muscles may be related to discogenic low back pain (DLBP), but their relationship is still unclear. The purpose of this study was to assess the paraspinal muscle fat infiltration in patients with DLBP by quantitative MRI, and to develop a novel DLBP rat model to explore the potential relationship between DLBP paraspinal muscle fat infiltration and TNF-α levels. We measured the proton density fat fraction (PDFF) of the multifidus and erector spinae muscles of 70 DLBP patients and 36 healthy volunteers by using quantitative MRI IDEAL-IQ. In addition, we developed a DLBP experimental rat model by puncturing the IVDs under the guidance of X-ray fluoroscopy. Then behavioral experiments were used to evaluate the pain and muscle dysfunction in rats. Through quantitative MRI and histological examination, the degeneration of IVDs and fat infiltration in the muscles were observed in vivo and in vitro. ELISA detects the level of TNF-α in rat IVDs and paraspinal muscles. In the human study, compared with healthy volunteers, the PDFF of multifidus and erector muscles of DLBP patients increased significantly at L4/5 and L5/S1 levels (p<0.05). In the rat experiment, compared with control group and sham group, DLBP group had reduced gait score, shortened response time to cold and heat stimuli, prolonged bending time, and shortened struggling time. The T2 signal intensity of punctured IVDs were progressively decreased. Histological examination revealed that IVDs had typical pathological changes of degeneration. The PDFF of multifidus muscle in the DLBP group were more than that in other groups (p<0.05), and muscle bundle space of the DLBP group muscles increased, and the muscle tissues increased lipid droplets. Finally, the expression of TNF-α in IVDs and paraspinal muscles in the DLBP group were significantly higher than that in the control group (p<0.05). It is reliable and feasible to establish a DLBP rat model by puncturing the lumbar IVDs under the guidance of X-ray fluoroscopy. The degeneration of lumbar IVDs with DLBP leads to the occurrence of fat infiltration of paraspinal muscles, which is related to the expression of TNF-α.